Crisis Team Management in a Scarce Resource Setting: Angkor Hospital for Children in Siem Reap, Cambodia - Henker, Richard Alynn; Henker, Hiroko; Eng, Hor; O’Donnell, John; Jirativanont, Tachawan (Frontiers in Public Health, 2017)
Introduction: A Crisis Team Management (CTM) simulation course was developed by volunteers from Health Volunteers Overseas HVO for physicians and nurses at Angkor Hospital for Children (AHC) in Siem Reap Cambodia. The framework for the course was adapted from Crisis Resource Management(Cheng, Donoghue, Gilfoyle, & Eppich, 2012; Gaba, 2010), Crisis Team Training(DeVita, Schaefer, Lutz, Dongilli, & Wang, 2004) and TeamSTEPPs© models(Quality., 2016). The Crisis Team Management course focused on teaching physicians and nurses on the development of team performance knowledge, skills and attitudes. Challenges to providing this course at AHC included availability of simulation equipment, cultural differences in learning and language barriers. The purpose of this project was to evaluate the impact of a CTM simulation course at AHC on attitudes and perceptions of participants on concepts related to team performance. Methods: Each of the CTM courses consisted of 3 lectures, including team performance concepts, communication, and debriefing followed by rotation through 4 simulation scenarios. The evaluation instrument used to evaluate the AHC CTM course was developed for Cambodian staff at AHC based on TeamSTEPPs© instruments evaluating attitude and perceptions of team performance(Castner, 2012). Crisis Team Management team performance concepts included in lectures, debriefing sessions and the evaluation instrument were: team structure, leadership, situation monitoring, mutual support and communication. The Wilcoxon sign rank test was used to analyze pre and post-test paired data from participants in the course. Results: Of the 54 participants completing the 3 CTM courses at AHC, 27 were nurses, 6 were anesthetists, and 21 were physicians. Attitude and perception scores were found to significantly improve (p<0.05) for team structure, leadership, situation monitoring and communication. Team performance areas that improved the most were: discussion of team performance, communication and exchange of information. Conclusions: Teaching of non-technical skills can be effective in a setting with scarce resources in a South Eastern Asian country.